2004
DOI: 10.1177/089686080402400206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fill Volume on Peritoneal Clearances and Cytokine Appearance in Peritoneal Dialysis

Abstract: Background Current adequacy guidelines for peritoneal dialysis encourage the use of large fill volumes for the attainment of small solute clearance targets. These guidelines have influenced clinical practice in a significant way, and adoption of higher fill volumes has become common in North America. Several studies, however, have challenged the relevance of increasing small solute clearance; this practice may result in untoward consequences in patients. Objective The present study was designed to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
2
14
2
Order By: Relevance
“…In supine position, an increase in DBP was demonstrated both with 2 l and 3 l fills compared with the drained situation. This is in accordance with Ventura et al, who demonstrated that increasing fill volume increases DBP [15]. Moreover, it has recently been shown that a fill with 3.86% glucose induces a comparable increase in blood pressure shortly after installation [2,16].…”
Section: Supine Positionsupporting
confidence: 91%
“…In supine position, an increase in DBP was demonstrated both with 2 l and 3 l fills compared with the drained situation. This is in accordance with Ventura et al, who demonstrated that increasing fill volume increases DBP [15]. Moreover, it has recently been shown that a fill with 3.86% glucose induces a comparable increase in blood pressure shortly after installation [2,16].…”
Section: Supine Positionsupporting
confidence: 91%
“…As for the role of dialysis dose on plasma TNF-α, our data showed that plasma TNF-α inversely correlated with Kt/V, suggesting that circulating TNF-α may be removed by PD, or plasma TNF-α production may be increased with a decrease in dialysis dose. Given the previous data showing that circulating cytokines with high molecular weights higher than 15 kDa are unlikely to be removed by peritoneal clearance [ 28 ], it is more likely that the production of TNF-α (molecular weight 17 kDa) may be increased in proportion to uremic toxins in blood, resulting in the inverse relationship between plasma TNF-α levels and Kt/V.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring IAP may also have other benefits in the PD patient population such as determining whether there is any impact on ultrafiltration rates, cardiac filling pressures, or feelings of fullness. 13-15 Furthermore, having an easy-to-use method to measure IAP at the bedside might allow for the use of pressure as a therapeutic guide to the PD prescription, as opposed to volume. This might have particular relevance in children.…”
Section: Discussionmentioning
confidence: 99%